Mapping Research on Local Wisdom in Environmental Management: A Global Bibliometric Study - Nurfadilah; Rezkawati Saad; Fahrunnisa; Musdalifah Syahrir (Journal of Local Wisdom in Education, 2025)
Environmental degradation and sustainability challenges have intensified the need for environmental management approaches that are socially and culturally grounded. Local wisdom, understood as indigenous and community-based knowledge, norms, and practices, has increasingly been recognized as a critical component of sustainable environmental management. However, existing studies remain fragmented and lack a comprehensive global overview. This study aims to map the development of research on local wisdom in environmental management through a global bibliometric analysis. Using a bibliometric mapping approach, data were retrieved from the Scopus database on Nov 14, 2025, resulting in 2,784 English-language, peer-reviewed documents published between 2021 and 2025. The analysis was conducted using Microsoft Excel, VOSviewer, and Biblioshiny to examine publication growth, leading sources, prominent authors, contributing countries, and thematic structures. The results reveal a steady increase in research output, with Indonesia emerging as the dominant contributor in terms of publications, institutions, and authorship. Conference proceedings constitute the main dissemination channels, while keyword analysis indicates a thematic shift from descriptive cultural studies toward sustainability, governance, decision making, and educational integration. The novelty of this study lies in repositioning local wisdom as a structured and evolving scientific field rather than isolated case-based research. The findings contribute theoretically by clarifying the intellectual structure and development trajectory of local wisdom research and practically by highlighting its relevance for environmental education and culturally responsive pedagogy. This study provides strategic insights for researchers, educators, and policymakers to strengthen the integration of local wisdom into sustainable environmental management and education.